2021
DOI: 10.1016/j.jhepr.2020.100214
|View full text |Cite
|
Sign up to set email alerts
|

TGR5 controls bile acid composition and gallbladder function to protect the liver from bile acid overload

Abstract: Background & Aims As the composition of the bile acid (BA) pool has a major impact on liver pathophysiology, we studied its regulation by the BA receptor Takeda G protein coupled receptor (TGR5), which promotes hepatoprotection against BA overload. Methods Wild-type, total and hepatocyte-specific TGR5-knockout, and TGR5-overexpressing mice were used in: partial (66%) and 89% extended hepatectomies (EHs) upon normal, ursodeoxycholic acid (UDCA)- or cholestyramine (CT)-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 31 publications
2
29
1
Order By: Relevance
“…This can be a clinically significant change because it has been increasingly recognized that NASH patients show elevated intrahepatic bile acids and serum bile acids and that hepatic bile acid burden contributes to hepatic inflammation and injury not only in NASH 23 , 29 , 30 , 31 , 32 but also alcoholic liver disease 21 and liver regeneration. 33 In contrast to mice, the human bile acid pool is more hydrophobic, and intrahepatic retention may exert a higher degree of hepatotoxicity by causing organelle stress, inflammatory infiltration, and stellate cell activation. 34 , 35 Consistently, the beneficial effects of the FGF19 analogue NGM282 in NASH patients was thought to be partly attributed to reduced hepatic bile acids and bile acid pool.…”
Section: Discussionmentioning
confidence: 99%
“…This can be a clinically significant change because it has been increasingly recognized that NASH patients show elevated intrahepatic bile acids and serum bile acids and that hepatic bile acid burden contributes to hepatic inflammation and injury not only in NASH 23 , 29 , 30 , 31 , 32 but also alcoholic liver disease 21 and liver regeneration. 33 In contrast to mice, the human bile acid pool is more hydrophobic, and intrahepatic retention may exert a higher degree of hepatotoxicity by causing organelle stress, inflammatory infiltration, and stellate cell activation. 34 , 35 Consistently, the beneficial effects of the FGF19 analogue NGM282 in NASH patients was thought to be partly attributed to reduced hepatic bile acids and bile acid pool.…”
Section: Discussionmentioning
confidence: 99%
“…5,39,40 Partly consistent with this, our data showed that the injection of an agonist of FXR (obeticholic acid) increased BA transport and reabsorption, while the injection of an antagonist of FXR (guggulsterone) decreased them. Previous studies produced contradictory results: TGR5-KO mice exhibited enhanced BA synthesis and weakened BA transport, 41,42 but Tgr5 −/− mice exhibited decreased expression of BA synthesis genes. 6 Our study also found a decreased expression of BA transport genes in the TGR5 inhibition treatment.…”
Section: Discussionmentioning
confidence: 90%
“…The membrane-bound G protein-coupled receptor TGR5 is ubiquitously expressed in various tissues such as intestine, liver and gallbladder ( Cipriani et al, 2011 ; Bidault-Jourdainne et al, 2021 ). In contrast to FXR, TGR5 mainly binds secondary BAs.…”
Section: Ba Receptors Have An Ambiguous Role In Shaping the Microbiome Liver Function And Inflammatory Responsementioning
confidence: 99%